PENGARUH MEDIA VIDIO ANIMASI TERHADAP PENINGKATAN BERPIKIR KRITIS SISWA KELAS 1 PADA PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN SAINTIFIK DI SD NEGERI 25 BANDA ACEH - Tiara Nabila; Ahmad Nasriari; Tria Marvida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of using animated video media on improving the critical thinking skills of first grade students in Mathematics learning using a scientific approach at SD Negeri 25 Banda Aceh. The background of this study was based on the low level of students’ critical thinking skills, which was caused by the less optimal use of attractive learning media that are suitable for the characteristics of elementary school students. This research employed a quantitative approach using an experimental method with a One Group Pre-test Post-test Design. The research subjects were 32 students of class I B at SD Negeri 25 Banda Aceh. Data were collected through tests (pretest and posttest) and observations. The test instrument was used to measure students’ critical thinking skills before and after the implementation of learning using animated video media through a scientific approach. Data were analyzed using the Shapiro–Wilk normality test and the Paired Sample t-test hypothesis test with a significance level of 0.05. The results showed that the average posttest score of students’ critical thinking skills was higher than the average pretest score. The results of the Paired Sample t-test indicated a significance value (Sig. 2-tailed) of 0.000 < 0.05; therefore, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Thus, it can be concluded that the use of animated video media has a significant effect on improving first grade students’ critical thinking skills in Mathematics learning using a scientific approach at SD Negeri 25 Banda Aceh